Ask your guides : connecting to your divine support system - Choquette, Sonia (Carlsbad, Calif. : Hay House, 2006)
We're all spiritual beings with a spiritual support system on the Other Side. This support system oversees and helps guide our lives from the instant we're born to the moment we leave our physical bodies and return to Spirit. Not knowing this fact is a severe handicap, as the Universe is designed to care for and nurture all its creatures and help make our lives naturally fall into a pattern of ease and flow, during which we nurture our souls, fulfill our life's purpose and make your time on Earth endlessly entertaining
Recognize your spirit first -- Entering the wide world of spirit -- Guardian angels, your personal bodyguards -- The archangels -- The ministry of angels -- Living with angelic influences -- Guides: who are they, and where do they come from? -- Getting ready to meet your spirit guides -- Making initial contact with your guides -- A step further: writing to your guides -- Learning to see your guides -- The spirit guides of the nature kingdom -- Your runners -- Your helpers -- Healer guides -- Teacher guides -- Animal guides -- Joy guides -- Light beings -- Negative entities -- Your spirit guides are closer than you think -- Guides work with messengers, too -- Spirit speak -- Your guides' names -- Guides help you they don't do your work for you -- Speaking to your guides through oracles -- Oracle divination decks -- Your higher self: the greatest guide of all -- Following your guides can be challenging -- Good news vs. guidance -- Finding believing eyes -- Afterword: thank your guides.
Keywords: Guides (Spiritualism); Guardian angels